DAMPAK PENGEMBANGAN PERKEBUNAN KEMIRI TERHADAP KESEJAHTERAAN SOSIAL-EKONOMI MASYARAKAT DESA MORBA DI KECAMATAN ALOR BARAT DAYA - Lutgardis Soi Maure; Lodia Mardina Kamengko; Herlofina Manikafola; Petrus Mau Tellu Dony (JOURNAL OF COMMUNITY DEDICATION, 2026)
This study aims to analyze the impact of candlenut plantation development on the socio-economic conditions of the Morba Village community. This study used qualitative methods with data collection techniques through interviews, observations, and documentation studies. These interviews were conducted in Morba Village, Alor Barat Daya District, Alor Regency, East Nusa Tenggara Province. The interviews indicated that candlenut is one of the largest sources of income for the Morba Village community. The development of candlenut plantations in Morba Village has shown significant growth in recent years. The area of ​​candlenut plantations is 20 hectares, with an average candlenut harvest of 10 tons in 2025. The development and production of candlenut plantations have positive economic and social impacts, such as increased income, job creation/reduced unemployment, expanded community economic activities, improved family welfare, and increased public awareness of sustainable natural resource management.